Selection of graphene dopants for Na3V2(PO4)3 graphene composite as high rate, ultra long-life sodium-ion battery cathodes - Jiang, Haifeng (2021)
Na3V2(PO4)3 (NVP) is one of the most promising cathode materials for sodium-ion batteries because of its stability, safety, and high reversible capacity. However, the sluggish Na-ion diffusion and poor electronic conductivity of NVP often hinder electrochemical performance, thus requiring compositing with carbon materials, such as graphene to improve the material. In this work, the effect of doping species of graphene on the electrochemical performance of NVP/graphene composites was systematically investigated and vigorously compared. 3D porous NVP fabricated by sol-gel method with 3 nm of carbon coating layers was deposited on graphene sheets with different surface functionalities (GO, N-rGO and P-rGO). NVP/N-rGO composites have low charge transfer resistance and high Na+ diffusion coefficient than that of NVP powder, NVP/P-rGO, and NVP/GO, which delivered a specific capacity of 113.9 mAh g−1 at 0.5C with a capacity retention up to 88.42% after 5000 cycles at 20 C. The superior sodium storage performance derives from the pyridinic and pyrrolic N doping in graphene, which triggers defective and active site numbers but maintains moderate graphitization to accelerate the Na+ and electron transportation.